2008
DOI: 10.1590/s0102-311x2008001300015
|View full text |Cite
|
Sign up to set email alerts
|

Acesso e acolhimento na atenção básica: uma análise da percepção dos usuários e profissionais de saúde

Abstract: This article is part of the evaluation study on the Project for Expansion and Consolidation of the Family Health IntroduçãoA Estratégia Saúde da Família busca romper com paradigmas cristalizados e incorpora novo pensar e agir na perspectiva de mudança e conversão do modelo assistencial. Dessa forma, possibilita a entrada de cenários, sujeitos e linguagens no âmbito da atenção à saúde com potenciais para reconstrução das práticas. Nessas, o cuidado deve considerar o princípio da integralidade e o usuário como p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
75
0
134

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(222 citation statements)
references
References 9 publications
3
75
0
134
Order By: Relevance
“…No seu estudo, Haggerty menciona que, em uma pesquisa nacional sobre acesso aos serviços de cuidados de saúde, 18,8% dos canadenses relataram ter dificuldades para acessar esses serviços para problemas de saúde agudos em 2001, e estes índices aumentaram para 24,2% em 2003. Outros estudos que utilizam metodologias diversas 25 reforçam esse resultado, apontando que o primeiro contato dos usuários com o sistema ainda apresenta barreiras a serem superadas.…”
Section: Discussionunclassified
“…No seu estudo, Haggerty menciona que, em uma pesquisa nacional sobre acesso aos serviços de cuidados de saúde, 18,8% dos canadenses relataram ter dificuldades para acessar esses serviços para problemas de saúde agudos em 2001, e estes índices aumentaram para 24,2% em 2003. Outros estudos que utilizam metodologias diversas 25 reforçam esse resultado, apontando que o primeiro contato dos usuários com o sistema ainda apresenta barreiras a serem superadas.…”
Section: Discussionunclassified
“…This is worrying, especially in relation to the main point of access, where the majority of activities to avoid well-structured network, in which primary health care was provided by pediatricians, demonstrate the need for fresh adjustments to enable the new model to be understood and legitimized. 5,22 The main criticisms of the new model which emerged from the mothers' statements were the lack of doctors The infant death case study revealed the ESF's failure to monitor at risk children as one of the main determinants of infant death as well as indicating the link between other lapses in the health care provided, such as diffi culties in working in teams. The fact that responsibility for the death was avoided and blame placed on the mother refl ects serious problems in communication and professional conduct as well as probable corporate issues.…”
Section: Discussionmentioning
confidence: 99%
“…The results show an attitude more of resignation on the part of the mothers, towards the miserable conditions of the context which overcame the perception of obstacles to health care access. 9,12,13,20,22,24 They also refl ect a position of little solidarity, based on the impersonality of the guiding question, which referred to the deaths of the children of mothers they did not know, which contributed to the development of blame in their statements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Aging in developing countries, like Brazil, is not always accompanied by healthcare modifications that meet the needs of this age stratum. 4,5 There is an increased demand for health services among the elderly, 6 and among the various aspects of health, oral health deserves special attention, as dental services have not historically prioritized this population group. Lack of knowledge and awareness may influence the oral health condition and the self-care of this population.…”
Section: Introductionmentioning
confidence: 99%